Studies on Tree-crop Interaction in Populus deltoides 'G-3' Bund Plantation under Irrigated Conditions - Sharma, K. K.; Singh, R. K. (Indian Forester, 1992)
Growth and yield of wheat crop as influenced by single row bund plantation of Populus deltoides 'G-3' grown on southern aspect of the field in east-west direction were investigated. Results show that wheat grain yield improves in the vicinity of trees. The other crop parameters have shown no significant difference between different distance treatments. The total income from 21 trees works out to be Rs. 8.70000 at 6 years of age. An increase of about 10.63 kg in wheat grain yield in a zone of 15 m from tree line was found.